Analysis of Critical Thinking Ability and Understanding of Basic Science Concepts in Primary School Teacher Education Students - Yopi Malagola; Supartinah; Setyo Eko Atmojo; Anwar Senen (Jurnal Penelitian Pendidikan IPA, 2023)
Students are not encouraged to develop their thinking skills, and learning in class is only directed at memorizing information. In addition, it is important for Primary School Teacher Education (PGSD) students who will become elementary school teacher candidates to have good critical thinking skills and a good understanding of basic science concepts. This study describes the ability to think critically and understand basic science concepts in PGSD students at PGRI Yogyakarta University. This research is a quantitative descriptive study using survey methods. The population of this study was second- semester PGSD students at PGRI Yogyakarta University. The research sample consisted of 77 second-semester PGSD students. The data analysis technique used in this study was descriptive analysis by measuring and describing the results of critical thinking skills and understanding basic science concepts. The results of this study indicate that the highest percentage of achievement is on the indicator of critical thinking skills, namely providing simple explanations, with a percentage of 75.45% with high criteria, and the indicator of understanding concepts with the highest percentage, namely the indicator of remembering with a percentage of 87.98% with very high criteria.